Attenuation of Oxidative Stress by Ischemic Preconditioning in an Experimental Model of Intraabdominal Hypertension. (3rd September 2015) - Leventi, Aikaterini; Argyra, Eriphylli; Avraamidou, Alexandra; Marinis, Athanasios; Asonitis, Spyridon; Perrea, Despoina; Voros, Dionysios; Theodoraki, Kassiani
ABSTRACT: Purpose: Increased intra-abdominal pressure, as used in laparoscopic surgery or seen in intraabdominal hypertension (IAH), is associated with tissue ischemia and oxidative stress. Ischemic preconditioning (IP) is a method successfully used in liver and transplant surgery, in order to attenuate the detrimental effects of ischemia and reperfusion. In this experimental study, we tested the ability of IP to modify oxidative stress induced by extremely high intraabdominal pressures. Methods: Twenty-five female pigs were studied and divided in three groups: a control group, a pneumoperitoneum group (with pressure of 30 mmHg), and an ischemic preconditioning group (initially subjected to preconditioning with pressure of 25 mmHg for 15 min and desufflation for 15 min and then to pneumoperitoneum as in pneumoperitoneum group). Blood samples were obtained at identical time intervals in the three groups. Total oxidative capacity, total antioxidative capacity and total nitric oxide (NO), nitrite and nitrate concentrations were measured and compared between groups. Results: IP increased total antioxidative capacity ( p = .045) and protective mediators like nitrite ( p = .022). It was also associated with a trend toward lower levels of total oxidative capacity at the end of the abdominal desufflation period but statistical significance was not met. Conclusions: IP attenuated oxidative stress induced by IAH, mainly by increasing antioxidative capacity and the levels of protective mediators. The fact that IP was effective, even when used at extremely high levels of intraabdominal pressure, reinforces the interest on this method but further studies are needed to clarify its mechanism of action and potential clinical applications.